The answer here is that x = 6 and y = 5. Here is how you can find this:

The thing to do here is to take the value that you have been given for x in the second equation and substitute it into the first equation. So then you have

3 (2y - 4) - 2y = 8

6y - 12 - 2y = 8

4y = 20

y = 5

Now you take this value of y and substitute it back in to the second equation to find x.

x = 2 (5) - 4

x = 10 - 4

x = 6

The given simultaneous equations are:

3x - 2y = 8 ... (1)

and

x = 2y - 4

The above equation can be expressed as:

x - 2y = - 4 ... (2)

Subtracting equation (2) from equation (1) we get:

3x - x - 2y + 2y = 8 + 4

2x = 12

Therefore:

x = 12/2 = 6

Substituting this value of x in equation (1):

3*6 - 2y = 8

18 - 2y = 8

-2y = 8 - 18 = -10

Therefore:

y = -10/(-2) = 5

Answer:

x = 6, y = 5

The set of equations 3x-2y=8 and x=2y-4 has to be solved for the variables x an y. It is possible for us to determine a unique solution as the number of variables is equal to the number of equations.

From x = 2y - 4, substitute for x in 3x - 2y = 8

3*(2y - 4) - 2y = 8

6y - 12 - 2y = 8

4y = 20

y = 5

x = 2y - 4 = 10 - 4 = 6

The solution of the given set of equations is x = 6 and y = 5

3x -2y = 8

x = 2y - 4

First, In the second equation subtract 2y on both sides of the equation

By subtracting, you should get

**3x - 2y = 8**

**x - 2y = -4** now subtract -2y with -2y ( which means subtract 3x with " x " and and 8 with -4 )

By subtracting, you should get

**2x = 12** now divide both sides by 2

By dividing, you should get

**x = 6 **which is your answer for " x "

now plug 6 into one of the equation

**6 = 2y - 4 **now add 4 on both sides

By adding, you should get

**10 = 2y **now divide both sides by 2

By dividing you should get

**y = 5 **which is your answer for " y "

So your answer is x = 6. Y = 5

(a) 3x-2y=8

(b) x=2y-4

Rearrange b: -x + 2y = 4

Add a and the rearranged b, solve for x:

-x + 2y = 4

+

3x - 2y = 8

-------------------

2x = 12 ----> x = 6

Plug in this value of x into one of the equations (a) or (b) and solve for y.

2y - x = 4

2y = 4 + x

y = (4 + x)/2

y = ( 4 + 6 ) / 2 = 5

3x-2y=8 x=2y-4 Solve for x and y

3(2y-4) -2y = 8

6y - 12 - 2y = 8 (now you combine the like terms)

6y (-12 +12) -2y = (8+12)

6y - 2y = 20

4y = 20 (divide both sides by 4)

**y = 5**

- now since you have the y value, just plug it in

x = 2(5) - 4

**x = 6**

**Now plug it in to check**

3x-2y=8

3(6) - 2(5) = 8

18 - 10 = 8

8 = 8

3x-2y=8

x=2y-4

3(2y-4)-2y=8

6y-12-2y=8

6y-12-2y+12=8+12

6y-2y=20

4y=20

4y/4=20/4

y=5

2(5)-4=x

x=6

So x=6 and y=5

The value for x is given as x=2y-4

So by substituting the value for x in the equation 3x-2y=8 it can be expressed as

3 x (2y-4) -2y = 8

6y-12-2y = 8

4y = 12+8

4y = 20

**y=5**

Now, substitute the value of y in the equation 3x-2y=8

3x-2 x 5 =8

3x-10=8

3x =10 + 8

3x=18

**x=6**

**Answer: X=6 and y=5**

To solve:

3x-2y=8..............(1)

x= 2y-4...............(2)

Solution:

We use the method of substitution , as in the second equation there is x given as subject:

x=2y-4 could be substituted in the first equation, So, the 1st equation is rewritten as below:

3(2y-4)-2y =8. This is an equation in one variable y. We collect y on one side and numbers on the other side.

6y-12 -2y=8

4y = 8+12 = 20. Or y = 20/4 = 5 .

x = 2(5)-4 = 6.

So x= 6 and y = 7.